2013
DOI: 10.7314/apjcp.2013.14.3.2137
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for U.S. Preventive Services Task Force (USPSTF) Recommendations Against Routine Mammography for Females between 40-49 Years of Age

Abstract: Breast cancer is the most common cancer among females, worldwide, accounting for 22.9% of all cancers (excluding non-melanoma skin cancer) in females. Mammography is a sensitive (77-95%) and specific (94-97%) screening method for breast cancer. Previously, females between the 40-50 years old were recommended to have mammograms every one to two years. However, based on current evidence, in 2009, USPSTF recommended that the decision to start regular, biennial screening mammography for females younger than 50 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Breast cancer accounts for 22.9% of all cancers in women [ 1 ]. It is a hormone-dependent disease, with estrogens playing a dominant role in both cancer initiation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer accounts for 22.9% of all cancers in women [ 1 ]. It is a hormone-dependent disease, with estrogens playing a dominant role in both cancer initiation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…However, women usually do not attend screening programs because of a lack of education and information. We also noted inadequate mammography screening in our analysis [1214]. …”
Section: Discussionmentioning
confidence: 94%
“…The inadequacy of mammography screening programs has led to the diagnosis of women with breast cancer in the late stages, and it has been found that the five-year survival rate falls to the range of 10-40% (15,16). In 2014, the World Health Organization prepared guidelines for breast cancer, 40-49 age group, 50-69 age group, and 70-74 age group (3).…”
Section: Discussionmentioning
confidence: 99%